Distribution of Hepatitis C Virus Genotypes in Canada: Results from the LCDC Sentinel Health Unit Surveillance System - RK Chaudhary; M Tepper; S Eisaadany; Paul R Gully (Canadian Journal of Infectious Diseases)
In a sentinel hepatitis surveillance study conducted by sentinel health units, 1469 patients were enrolled, and 959 (65.3%) were positive for antibody to hepatitis C virus (HCV). Samples from 387 patients (40.4%) were tested for HCV RNA, and 289 (74.7%) were positive for RNA. The major risk factor for HCV infection was injection drug use, reported in 71% of cases. The genotyping of HCV isolates showed that subtype 1a (48%) was predominant in Canada. The other subtypes detected were 1b (19%), 2a (6%), 2b (3%), 3a (22%) and 4a (1%). In Winnipeg, Manitoba, subtype 3a (47%) was more prevalent than subtype 1a (37%), and, in Guelph, Ontario, both subtypes 1a and 3a had equal (40%) distribution. The prevalence of subtype 3a was significantly higher in injection drug users (27%) than in nonusers (10%) (P<0.005). In Canada, injection drug use is the major risk factor for HCV infections, and subtype 1a is more prevalent.